THE POWER OF SIXTY WORDS IS THE MAIN SONG OF THE PEOPLE OF THE COUNTRYANTHEM OF INDEPENDENCE AND PROSPECT - Makhmudov, Jakhongir Saminjon ugli (Educational Research in Universal Sciences, 2023)
This article talks about the anthem of independence and perspective, which is the main song of the people of the country, the power of sixty words.